Developmental disorders and altered gene expression in the tropical clawed frog (Silurana tropicalis) exposed to 17α‐ethinylestradiol. Issue 9 (6th November 2012) - Hirakawa, Ikumi; Miyagawa, Shinichi; Mitsui, Naoko; Miyahara, Maki; Onishi, Yuta; Kagami, Yoshihiro; Kusano, Teruhiko; Takeuchi, Takashi; Ohta, Yasuhiko; Iguchi, Taisen
ABSTRACT: Several endocrine‐disrupting chemicals with estrogenic activity can affect sexual development and reproduction in aquatic wildlife. The occurrence of oocytes in the testis (testis‐ova) is one reproductive disorder and can be used as a valid endpoint when studying disruptive effects of estrogenic chemicals. To elucidate the molecular basis of testis‐ova induction, we conducted gene expression analysis in the gonads of Silurana tropicalis exposed to 0, 3, 10 and 30 ng l −1 17 α ‐ethinylestradiol (EE2) from 2 days after fertilization to the juvenile stage (14 weeks after fertilization). The frequencies of testis‐ova induction or male to female sex‐reversal of the gonads increased in an EE2 dose‐dependent manner. Microarray analysis showed that expressions of a large number of genes were significantly changed by EE2 exposure. Genes including egg envelope composition ( zp4, zpax, zpc, zp3 . 2 and egg cortical granule lectin ), 42S particle genes ( 42Sp50, 42Sp43 and 42Sp48 ) and regulation of female germ cells ( figla ) are associated with the testis‐ova and sex‐reversal situation in the gonads. Of those, expression of zpc and 42Sp50 genes is associated with testis‐ova. Thus, we propose that these genes are useful biomarkers for toxicological research in amphibians developmentally exposed to estrogenic chemicals. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : The occurrence of oocytes in the testis (testis‐ova) is one reproductive disorder and can be used as a valid endpoint when studying disruptive effects of estrogenic chemicals in fish and amphibians. Gonads of the genetically male tropical clawed frog (Silurana tropicalis) exposed developmentally to 17α‐ethinylestradiol were analyzed using histopathology, microarray and quantitative PCR. Expression of zpc and 42Sp50 genes was demonstrated to be associated with testis‐ova in the S. tropicalis .